KÓRKEM SÓZ SHEBERLERI TILDEGI SINONIMLERDIŃ PAYDA BOLÍW DEREGI - Orazımbetov, A.Q. (SCIENCE and SOCIETY, 2022)
This article states that the contextual synonyms used by the masters of the artistic word, along with ensuring the artistry and expressiveness of works, in the process of long-term use in the language form absolute synonyms and influence the development of the literary language.